2019
DOI: 10.1038/s41366-019-0333-0
|View full text |Cite
|
Sign up to set email alerts
|

Childhood growth patterns and cardiovascular autonomic modulation in midlife: Northern Finland 1966 Birth Cohort Study

Abstract: Objectives: To test the hypothesis that age and body mass index (BMI) at BMI peak during infancy and at BMI rebound in childhood are related to cardiovascular autonomic modulation in adulthood. Methods: At the age of 46, a sample (n=5 861) of the participants of the Northern Finland Birth Cohort 1966 took part in follow-up examinations. Heart rate variability (HRV), baroreflex sensitivity (BRS) and low-frequency oscillations of systolic blood pressure (LFSBP) were measured during sympathetic stimulus by standi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…The HRV analysis has been confirmed as a useful and non-invasive technique to measure autonomic modulation in children [49]. Students' HR mean analysis revealed a tendency to decrease by grade whereas an incremental tendency in parasympathetic modulation (RMSSD, pNN50 and SD1) was found by grade and age, coinciding with previous researches [50,51]. These results might be in accordance with a normal maturation of autonomic nervous system where parasympathetic activation increases from birth to young adulthood [52,53].…”
Section: Discussionsupporting
confidence: 81%
“…The HRV analysis has been confirmed as a useful and non-invasive technique to measure autonomic modulation in children [49]. Students' HR mean analysis revealed a tendency to decrease by grade whereas an incremental tendency in parasympathetic modulation (RMSSD, pNN50 and SD1) was found by grade and age, coinciding with previous researches [50,51]. These results might be in accordance with a normal maturation of autonomic nervous system where parasympathetic activation increases from birth to young adulthood [52,53].…”
Section: Discussionsupporting
confidence: 81%
“… 9 Early life trends in adiposity [body mass index (BMI) and age at BMI peak and rebound) have also been associated with cardiovascular autonomic function in mid-life. 10 …”
Section: What Has It Found? Key Findings and Publicationsmentioning
confidence: 99%
“…There is growing evidence that the age at AP or AR has a predictive significance for obesity in later life. The current literature has shown that a later AP or an earlier AR is associated with the occurrence of overweight or obesity (6)(7)(8)(9) and the associated adverse health outcomes (insulin resistance/type 2 diabetes mellitus and cardiovascular disorders) in childhood, adolescence, or adulthood (6,7,(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%